Manufacturing and characterization of al-xmg-xmgo composites using stir casting process - Yilmaz, Musa; Kurt, Halil Ibrahim; Yilmaz, Necip Fazil (SPRINGER INT PUBL AG)
In this work, the Al-xMg-MgO composites were fabricated via stir casting method. The different amounts of Mg (1, 3 and 5 wt%) and MgO (0.5, 1.0 and 1.5 wt%) were added to the aluminum matrix, and the composites were casted at various temperatures of 700, 800 and 900 & DEG;C. The effects of the casting temperature (& DEG;) and the Mg (wt%) and MgO (wt%) ratios on the microstructure, physical and mechanical properties of the composites were investigated. The scanning electron microscope with electron-dispersive spectrum, density (g/cm(3)), porosity (%), hardness (HR-15T) and compression (MPa) test analyses were conducted on the composites. The results were also analyzed with the Taguchi experiment design method with ANOVA. The properties of the composites changed depending on the process parameters and ratios of Mg element and MgO particles. The minimum density and porosity contents were obtained as 2.62 g/cm(3) and 0.6%, respectively. The increase in the casting temperature contributed to the wettability and so the properties of the samples to some extent. The additions of Mg and MgO improved the hardness (72.8 HR-15T) and compression strength (646.4 MPa) of the composites. It can be said that the main strengthening mechanisms of the Al-xMg-xMgO composites for this study were the solid solution and dispersion strengthening mechanisms.
Keywords: AMCs; ANOVA; Taguchi; MgO; composite; aluminum